Implementation and Optimization of a Voucher-Based Internet Access System Using MikroTik RB941 for RT/RW Net Networks - Adelia Amanda; Alfridom Wau; Dede Priyandi Bawamenewi; Siti Rahmayani Sitorus; Romulo P Aritonang; Meiliyani Br Ginting (Karya Techno Solusindo, 2026)
The increasing demand for stable, secure, and affordable internet access in RT/RW Net environments requires more effective network management strategies. Although MikroTik-based hotspot systems have been widely implemented, many existing studies primarily focus on basic hotspot deployment without integrating bandwidth optimization and voucher-based user authentication into a unified network management framework. Consequently, network administrators continue to encounter challenges related to unequal bandwidth allocation, inefficient user management, and limited access control. This study aims to implement and optimize a voucher-based internet access system using the MikroTik RB941 router to improve bandwidth management, user authentication, and network administration in RT/RW Net networks. The research employed an experimental approach involving network design, router configuration, hotspot implementation, voucher generation, bandwidth management using the Per Connection Queue (PCQ) method, and system testing. The implementation utilized MikroTik RouterOS, Winbox, and Mikhmon to configure and manage the network services. The proposed system successfully established centralized user authentication, automated voucher management, and more organized bandwidth allocation under the implemented testing scenario. The novelty of this study lies in the integration of Time-Based and Volume-Based voucher management with PCQ bandwidth allocation within a single MikroTik RB941 framework, providing a more comprehensive network management approach than conventional hotspot implementations. The findings indicate that the proposed configuration provides a structured and practical solution for managing internet access in RT/RW Net environments and establishes a foundation for future evaluations of network performance using Quality of Service (QoS) parameters. REFERENCES Anwar, I. D., & Akbar, Y. (2024). Network Bandwidth Management with Per Connection Queue (PCQ) Method on Mikrotik at Masterpiece Family Karaoke Tebet. Indonesian Journal: Informatics and Communication Management, 5(3), 3125–3137. Aulia, B. W., Rizki, M., Prindiyana, P., & Surgana, S. (2023). The crucial role of computer networks and databases in the digital era. Journal of Information Systems and Information Technology, 1(1), 9–20. Darmawan, M. D., & Rudianto, R. (2025). Design and build internet billing based on using Mikhmon-based wifi vouchers. Jati (Journal of Informatics Engineering Students), 9(6), 9373–9381. Ernawati, D., & Setiawan, A. (2025). Implementation of a web-based Mikrotik hotspot voucher sales management information system to improve the efficiency of isk-net ISP services. Journal of Bhinneka Community Service, 4(2), 2406–2418. Faiha, H. (2024). Network Security Analysis Using Mikrotik Router OS to Optimize Computer Network Security in Improving the Quality of Public Services at the Lubuk Sikaping Religious Court Office with Port Knocking and ACL (Access Control List) methods. Fajaruddin, H., & Kurniawan, A. (2025). The use of wireless fidelity (Wi-Fi) technology in the development of RT-RW Net to grow the digital economy. National Journal of Informatics (June), 4(2), 42–49. Fauzi, R., Zainy, A., Lubis, I. S., Haqi, A. B., Akhir, A. Z., Kumana, B., Simamora, N., & Juliana, R. (2023). Installation of Mikrotik on Virtualbox and connection between Mikrotik in Virtualbox and Winbox at Smk S Teruna Padang Sidempuan. ADAM Journal: Journal of Community Service, 2(1), 106–118. Gunawan, G. G. I., & Alijoyo, F. A. (2024). Design and build a wifi voucher purchase application with a payment gateway and radius. Journal of Business Information Technology and Systems, 6(2), 310–321. Haqi, A. B., Siregar, D. A., Mutiara, M., Lubis, N. F., & Akhir, A. Z. (2023). Introduction to Basic Computer Networks at SMK Negeri 1 Batang Onang. ADAM Journal: Journal of Community Service, 2(2), 293–303. Ikhwandi, M. I., & Azinar, A. W. (2025). Wireguard implementation as a connection using mikrotik routing. Smatics Journal, 15(02), 292–301. Ismawati, I., & Softianto, S. (2025). Implementation of Mikrotik RouterOS-Based Voucher Hotspot System for Internet Access Management on LAN Networks. Karapan Network Journal: Journal of Computer Technology and Mobile Ad Hoc Network, 1(01). Lestyaningrum, I. K. M., Trisiana, A., Safitri, D. A., Pratama, A. Y., & Wahana, T. P. (2022). Global education based on digital technology in the millennial era. Unisri Press. Lukito, K. D., Liliana, L., & Palit, H. N. (n.d.). Creation of crowdsource applications for Android-based household services. Manuaba, I. B. K., Agus, F., Ramayu, I. M. S., Saputro, V. A., Pakpahan, A. V., Skawanti, J. R., & Judijanto, L. (2025). Computer Network. PT. Sonpedia Publishing Indonesia. Masruha, M. (2022). Islamic Law Perspective on the Voucher System at KPRI Nusa Indah. JURISY: Sharia Scientific Journal, 2(1). Mojasa, B. W. (2024). Criminal liability for misuse of RT/RW Net by using resold broadband internet. Journal of Legal Compilation, 9(2), 223–234. Nugroho, P. A. (2022). The design of the RT/RW Net computer network uses a Power Line (PLC) communication line in Taman Berdikari Sentosa housing. JEIS: Swadharma Journal of Electrical and Informatics, 2(1), 9–14. Prameswari, I. A., Noviyanti, Y., & Susilowati, T. (2024). Introduction to Information Systems. NEM Publishers. Putri, D. L., Pratama, A. R., & Nurjanah, L. (2025). Optimizing Digital Access through Internet Network Planning in Dawuhan Village. JUPAMU: Journal of Multidisciplinary Community Service, 1(1), 25–36. Rahman, R. (2024). Implementation of Mikrotik-Based RT RW Net Network Network and Hotspot Networks with Mikhmon Feature in Fast. Net. Rusyunizal, D., & Karim, H. A. (2025). Transparency of Web-Based Islamic Education Management System in the Digital Era. Journal of Educational Management, 10(4), 3319–3331. Sanjaya, R. (2020). 21 Reflections on Online Learning in Emergency Times. SCU Knowledge Media. Sari, A. I., Syaifuddin, M., & Andriani, T. (2023). Optimizing the strategic management of educational infrastructure. Journal of Multidisciplinary Sciences, 1(4), 814–822. Ulfa, H., Basuki, A. I., Suranegara, G. M., & Fauzi, A. (2024). DDoS Protection System for SDN Network Based on Multi Controller and Load Balancer. Systematic: Journal of Information Systems, 13(2), 555–571. Yusman, Y., Putra, R. R., & Sinaga, I. (2024). The application of information systems to improve governance and public services in the digital era. Compatible with Media Technology.